Correlation of sleep quality with fatigue and disease activity among patients with primary Sjögren’s syndrome: a cross-sectional study - Dardin, Luciana Paula; Garcia, Ana Beatriz Andreo; Gazoni, Fernanda Martins; Santos, Fania Cristina dos; Mello, Marco Tulio de; Trevisani, Virginia Fernandes Moça (São Paulo Medical Journal, 2020)
BACKGROUND: Fatigue is a frequent symptom in patients with primary Sjögren’s syndrome (pSS) and can be a cause of or be associated with sleep disorders. OBJECTIVE: To assess the sleep quality of pSS patients and its relationship with fatigue and disease activity. DESIGN AND SETTING: Analytical observational study conducted at an exercise psychobiology laboratory. METHODS: Sleep quality was evaluated using the Pittsburg sleep quality index (PSQI) and actigraphy. Fatigue was evaluated through the Profile of Fatigue and Discomfort – Sicca Symptoms Inventory (PROFAD-SSI-SF) and a visual analogue scale for fatigue (VAS-fatigue). Disease activity was evaluated using a visual analogue scale for pain (VAS-pain), EULAR Sjögren’s Syndrome Patient Reported Index (ESSPRI) and Disease Activity Index (ESSDAI). We summarized the data through descriptive statistics. RESULTS: A total of 50 female patients with pSS, of average age 56.4 years, were included in the study; 80% presented low disease activity. The total PSQI score showed that 74% had poor sleep. The actigraphy showed mean sleep latency of 26.2 minutes and mean nightly awakening of 48.2 minutes (duration of wakings after sleep onset, WASO). There were correlations between PSQI and VAS-pain, VAS-fatigue, PROFAD-SSI and ESSPRI. Actigraphy showed a correlation between the duration of WASO and ESSDAI. CONCLUSION: The present study provides important information regarding correlations between sleep disorders and disease activity. There is a need for proper control over disease activity and for development of strategies to help patients to sleep better in order to diminish their fatigue. CLINICAL TRIAL REGISTRATION: NCT03130062.